Hydroponic paddy nursery for healthy seedlings Compatible for mechanical transplanting - Saxena, Abha; Rai, Deepti (Indian Farming, 2021)
Paddy (Oryza sativa) is one of the most important cereal crops in India for food security. In the world market of 15 to 18 million tonnes (mt) of rice traded annually, basmati rice accounts for almost 10%. However, basmati rice generates three times higher returns (US$ 800-1,200 per tonne) than non-basmati rice ($ 200-400 per tonne) in both domestic market and international. However, the maximum permissible residue level (MRL) plays a crucial role in export. European Union (EU) cut the maximum residue limit for Tricyclazole from 0.10-0.01 ppm on 31 December 2017. Thus, it drastically affected the fate of 70,000-90,000 tonnes of rice exported per month. We have to evolve new agriculture technologies, methods to boost our export. Since healthy nursery is the basis of healthy crop, Ayurvet Research Foundation (ARF) had been raising the nursery through hydroponics (Soilless) agriculture and no chemical/pesticide/insecticide/fertilizer are used. Rice exporters are facing the problem of pesticide residue in the recent past, so starting with healthy, chemical-free nursery will lay the foundation for healthy, chemical-free rice.